SME Finance in Ethiopia : Addressing the Missing Middle Challenge - World Bank (Washington, DC, 2015)
This study starts with a brief analysis of which firms are the main net job creators in Ethiopia and then focuses on the financing constraints of Ethiopian Micro, Small and Medium Enterprises (MSMEs) as one of the key obstacles to job creation and growth. The study uses two demand-side and an ad-hoc supply side survey administered to 16 financial institutions. This survey allowed collecting data on the actual involvement of financial institutions with MSMEs, their perception of potential public policy approaches to enhance MSME access to finance and the adequateness of their current business models. The combination of both demand-side and supply-side analysis allows to gain a full picture of MSME finance practices in Ethiopia by connecting information on firm experiences with the reporting of financial institutions on their business practices. While there was already anecdotal evidence that small firms were lacking proper access to finance in Ethiopia, the value added of this study is to provide accurate empirical evidence of the existence of a missing middle phenomenon.